Love: a passion of the soul, an obsession, or an evolutionary disposition? - Borges, Maria (Sofia, 2023)
What is love? Sung by poets and musicians, the cause of the greatest joys and sorrows, love is difficult to define. In this text, I will present some ways of understanding love, beginning with the tradition of thinking of love as a passion of the soul. Second, I will present the physiological conception of love as defended in the book Love is the Drug. I will also consider a third way in which love is related to evolutionary strategies.
Keywords: love; passion of the soul; obsessive disorder; evolutionary disposition